Energy and protein intake at the Department of Cardiothoracic surgery, Landspítali – The National University Hospital of Iceland. Monitoring the implementation of a validated simple screening tool for malnutrition in hospitalized patients - Dagný Ösp Vilhjálmsdóttir 1984- (2013)
Background and Objective: Icelandic studies suggest that prevalence of malnutrition at Landspitali – The National University Hospital (LSH) is 20-60%, depending on patient groups. Malnutrition among patients is considered to increase risk of complications. The objectives of this thesis were: 1) To monitor the implementation of a validated simple screening tool for malnutrition (SSM) at LSH by assessing the number of patients screened in each month from December 2011 to November 2012, 2) To estimate energy and protein intake of patients at the Department of Cardiothoracic surgery, LSH and compare with estimated energy and protein requirements, and 3) To evaluate the method recommended for estimating energy and protein requirements in the Clinical Guidelines on Nutrition for Hospitalized patients at LSH. Methods: Number of screened patients was estimated each month from December 2011 to November 2012. Nutritional status was estimated using a simple screening tool for malnutrition (SSM), the patients who scored 0-2 points were categorized as well-nourished, those who scored 3-4 points were categorized as at risk of malnutrition and those who scored ≥5 points were categorized as malnourished. The screening was monitored at the Department of Cardiothoracic surgery, LSH. Subjects in the project related to aim two were patients admitted to the Department of Cardiothoracic surgery, LSH. The energy and protein content of meals served by the hospital‘s kitchen is known. Starting at least 48 hours after surgery, all leftover food and drinks were weighed and recorded for three consecutive days. Energy and protein requirements were estimated according to Clinical Guidelines on Nutrition for Hospitalized patients at LSH (25-30 kcal/kg/day and 1.2-1.5 g/kg/day, respectively). The accuracy of energy expenditure equations was estimated by viewing other studies (aim 3). Results: From December 2011 to November 2012 the number of screened patients per month was 17 and increased to being 288 per month. Number of screened patients ...